Work Ethics and Motivation of Public Elementary School Teachers in the District of Pontevedra - Rima Baril Capulso (IDEAS: Journal of Management & Technology, 2023)
Motivation and work ethics are critical elements of effective and efficient teaching and learning processes. The teachers can keep up the level of service they provide at work by practicing good work ethics. Teachers' drive for professional development and academic success comes from their motivation. This study assessed the work ethics and motivation of public elementary school teachers in the district of Pontevedra. The descriptive-correlational research design was employed in the study. 160 randomly chosen public elementary school teachers from the Pontevedra district served as the study's respondents. A researcher-made survey questionnaire that had been reliability tested and validated was used to collect the data. Frequency count, percentage, mean, t-test, analysis of variance, and Pearson's r were among the statistical techniques utilized to examine and interpret the data. The data demonstrated that the respondents had "excellent" work ethics and "very highly motivated" motivation. When they were divided into groups based on sex, age, highest educational attainment, and length of service, there were no appreciable differences in their level of work ethics. When they were categorized according to their highest educational attainment, there was a significant difference in their level of motivation; however, when they were grouped according to sex, age, and length of service, there were no significant differences. The work ethics and motivation of the public elementary school teachers in the Pontevedra district were significantly correlated.